Cerâmica romana importada na Foz do Douro : uma escavação arqueológica no Castelo de Gaia (V. N. Gaia, Norte de Portugal) - Silva, António Manuel S. P. (2018)
The hill known as Castelo de Gaia is one of the main places of ancient human occupation at Douros river mouth. An archaeological excavation that occurred there in 2008, due to a previous archaeological evaluation of a building project, led to the discovery of Roman ruins and relevant ceramic nds. is paper focuses the imported wares set, providing data to further analyse on certain vessels circulation and consumption in dierent moments of Roman presence in the region. Amongst the most ancient wares there are types of the 1st century BC, like Campanian amphorae used for wine trade. Several Late-Antique productions were also identied, like Oriental amphorae, as well as LRC ne wares and other imported table ceramic.